((E)-N?(3,5-di-tert-butil-2-hedroxybenzilidene)-2-hydroxybenzohydrazide (H3sahz)2 Copper (II) Complex: Synthesis, Crystal Structures, in silico Evaluations, and Enzymatic Inhibition - Fatullayeva, Perizad Amrulla; Mejidov, Ajdar Akper; Safronenko, Marina Gennadievna; Nikolayevich Khrustalev, Victor; Yalcin, Bahaddin; Sadeghian, Nastaran; Sadeghi, Morteza; Sadeghian, Nastaran (Wiley-V C H Verlag Gmbh, 2023)
In this study, (E)-N'(3,5-di-tert-butil-2-hedroxybenzilidene)-2-hydroxybenzohydrazide (H3sahz) 2 and its copper (II) complex has been synthesized and evaluated by methods FTIR, UV-Vis, EPR, and single crystal X-ray analysis. It has been shown, that H3sahz crystallizes as a dimer through hydrogen bonds. H3sahz with copper nitrate forms [Cu(H(2)sahz)(NO3)(H2O)] complex, which according to X-ray diffraction analysis has a distorted square pyramidal structure. The complex was screened for alpha-glucosidase (alpha-Glu), acetylcholinesterase (AChE), and butyrylcholinesterase (BChE) inhibitory abilities. Results displayed that IC50 and K-i values of the novel complex for AChE, BChE, and aGlu enzymes were obtained at 0.93-2.14, 1.01-2.03, and 73.86-102.65 mu M, respectively. The molecular docking outcomes have shown that the synthetic complex has a lower affinity for aglucosidase compared to acarbose. But the inhibition ability of H(3)sahz for acetylcholinesterase and butyrylcholinesterase enzymes was greater than that of tacrine. These findings indicate that the (H(3)sahz)(2) complex may be considered a possible candidate for the development and discovery of compounds effective in inhibiting the relevant enzymes.
Keywords: Bioactivity; Enzymes Inhibition; Molecular Docking; Salicylic Acid Hydrazide; X-Ray